Alzheimer's disease as an innate autoimmune disease (AD2): A new molecular paradigm. Issue 3 (27th September 2022) - Weaver, Donald F.
Abstract: A new model of Alzheimer's disease (AD) is presented: Alzheimer's disease as an autoimmune disease (AD 2 ). In response to pathogen‐/damage‐associated molecular pattern‐stimulating events (e.g., infection, trauma, ischemia, pollution), amyloid beta (Aβ) is released as an early responder cytokine triggering an innate immunity cascade in which Aβ exhibits immunomodulatory/antimicrobial duality. However, Aβ's antimicrobial properties result in a misdirected attack upon "self" neurons, arising from the electrophysiological similarities between neurons and bacteria in terms of transmembrane potential gradients and anionic charges on outer membrane macromolecules. The subsequent breakdown products of necrotic neurons elicit further release of Aβ leading to a chronic, self‐perpetuating cycle. In AD 2, amino acid (trp, arg) metabolism is a central control player in modulating AD autoimmunity. AD 2 includes Aβ as an important molecular player, but rejects the "amyloid hypothesis, " recognizing Aβ as a physiologically oligomerizing cytokine and part of a larger immunopathic conceptualization of AD.